2003
DOI: 10.1021/bm0341834
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Coatings of Endovascular Stents Based on Polyelectrolyte Multilayers

Abstract: Layer-by-layer self-assembly of two polysaccharides, hyaluronan (HA) and chitosan (CH), was employed to engineer bioactive coatings for endovascular stents. A polyethyleneimine (PEI) primer layer was adsorbed on the metallic surface to initiate the sequential adsorption of the weak polyelectrolytes. The multilayer growth was monitored using a radiolabeled HA and shown to be linear as a function of the number of layers. The chemical structure, interfacial properties, and morphology of the self-assembled multila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
290
1
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(305 citation statements)
references
References 38 publications
6
290
1
4
Order By: Relevance
“…12-14 However, these polymers present challenges due to their poor mechanical properties and limited ability to sustain stent expansion and deployment, often requiring crosslinking and related treatments to enhance durability, which in turn alters biological responses. [12][13][14] Silks represent a new family of advanced biomaterials, which should help to overcome some of these key limitations in both coated-stent technology and the favorable clinical outcomes possible. A naturally-occurring biopolymer, silk fibroin has high strength, mechanical toughness, robust flexibility, while sustaining excellent biocompatibility, therein presenting considerable utility for a number of difficult-to-solve human therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…12-14 However, these polymers present challenges due to their poor mechanical properties and limited ability to sustain stent expansion and deployment, often requiring crosslinking and related treatments to enhance durability, which in turn alters biological responses. [12][13][14] Silks represent a new family of advanced biomaterials, which should help to overcome some of these key limitations in both coated-stent technology and the favorable clinical outcomes possible. A naturally-occurring biopolymer, silk fibroin has high strength, mechanical toughness, robust flexibility, while sustaining excellent biocompatibility, therein presenting considerable utility for a number of difficult-to-solve human therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 In addition, recent studies have shown that there are many other promising applications for multilayered materials in such areas as drug delivery, sensors, wound healing, and membrane filtration. [19][20][21][22] Hyaluronic acid (HA) is a linear polysaccharide composed of repeating disaccharide units of D-glucuronic acid and N-acetyl-D-glucosamine. 23 In dilute solution the conformation of the HA chains can be converted from a random coil to a single helical structure with a change in pH or ionic strength.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembled multilayer architectures can be built by using macromolecules or materials as different as polyelectrolytes, proteins, inorganic complexes, clay platelets, or colloidal particles, all adsorbed from aqueous solutions or suspensions. Although complex multilayered architectures were shown to deliver a variety of molecules including drugs (4)(5)(6)(7)(8) and DNA (9)(10)(11)(12), it is unknown whether this technique is feasible for the sustained delivery of siRNAs.…”
mentioning
confidence: 99%